2017
DOI: 10.1002/adv.21914
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability, fire behavior, and fumes emission of polyethylene nanocomposites with halogen‐free fire retardants

Abstract: The synergism between nanoparticles and different kinds of halogen-free fire retardants leading to reduction in flammability and smoke generation of polyethylene was investigated. The composites were evaluated by thermogravimetric analysis, oxygen index test, cone calorimeter measurements, and a single-chamber test. Moreover, the semivolatile and volatile compounds evolved in the thermal degradation processes of polyethylene were determined using a steady state tube furnace and gas chromatograph with mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…It was observed that the carbonaceous char barrier was created on the surface of the sample. The residue had the form of swollen char and was shaped in layers [ 39 ]. The increased char yield worked as a physical char barrier, which could block the release of degradation volatiles to feed the flame, and thus, the HRR was slowed down [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the carbonaceous char barrier was created on the surface of the sample. The residue had the form of swollen char and was shaped in layers [ 39 ]. The increased char yield worked as a physical char barrier, which could block the release of degradation volatiles to feed the flame, and thus, the HRR was slowed down [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…This technique is used for characterization of the mechanical properties of the tested materials. DMTA is a method that measures the stiffness and mechanical damping of a cyclically deformed material as a function of temperature . The curves of the EPUUs annealed at 80 °C obtained from measurements using DMTA are shown in Figs (a), 6(b) and 6(c) for the storage modulus ( E ′), loss modulus ( E ′′) and loss tangent (tan δ ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…From analysis of the curve of loss modulus ( E ′′) (Fig. (b)), taking into account the shape, position and height of the peak, it is possible to determine the degree of order and a free movement of the polymer chains . While the modulus E ′ is proportional to the stored energy, modulus E ′′ is part of the energy converted into heat and irreversibly lost .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, polymers with an aliphatic backbone will generate a lower amount of smoke than polymers with pendant aromatic groups [ 214 ]. Carbon monoxide (CO), carbon dioxide (CO 2 ) hydrogen cyanide (HCN), hydrogen chloride (HCl), nitrogen oxides (NOx), sulphur dioxide (SO 2 ), aldehydes, polycyclic aromatic hydrocarbons (PAHs) and so forth, are the most common gases developed during thermal decomposition and combustion of polymeric materials [ 215 ]. Since FRs can act in the condensed (polymer breakdown, charring, intumescence) and/or in the gas (gas dilution, chemical quenching of active radicals) phase it is worth noticing that flame inhibition through the gas phase dramatically increases the yield of CO, smoke and toxic gases [ 216 , 217 ].…”
Section: Flame Retardant Chemistrymentioning
confidence: 99%